The Backbone Of The Language - Nizomiddin Mahmudov (International Journal Of Literature And Languages, 2025)
The Uzbek language is an objective image – both internal and external – that fully reflects the character and appearance of the Uzbek people, their world of thought and imagination, their past and present; importantly, this image is “drawn” by the language itself, through its own means and, as it were, by its “own hand.” The article discusses how this image has manifested itself throughout the processes of our people’s millennia-long linguistic and historical development, as well as in their unique cultural and intellectual, literary and artistic treasures.